Herramientas digitales en el proceso de aprendizaje de las matemáticas en estudiantes de tercer año de Educación General Básica - Moran Suarez, Dayana Lisbeth (2023)
For the mathematics learning process, it is essential to use innovative strategies, capable of facilitating the mathematics learning process, in a more interactive and dynamic way, such as digital tools, since they are a complement for the teacher to achieve that their students have meaningful. It started from the observation towards the third-year teacher of Basic General Education and it was verified that she does not use digital tools, like other teachers, so the students present difficulties in the learning process of mathematics, which is evidenced in their academic performance. The objective of this research work is to analyze the influence of digital tools in the learning process of mathematics in third-year students of basic general education. The methodology used was a mixed approach, with a descriptive and field scope. Techniques such as observing the mathematics teacher, the interview with teachers of the mathematics subject and the coordinator of the mathematics area, the student survey and the documentary review were applied to evaluate the academic performance of third-year students of education basic overview. As a result, it was obtained that digital tools improve and optimize the mathematics learning process, since it was confirmed that teachers who use digital tools obtained better results in the mathematics learning process, which is evidenced in academic performance of the students. Based on the results, a system of workshops was proposed in order to provide teachers with easy and simple digital tools to use in class.